38.9k views
0 votes
What’s -2(7n-6)+n=-3-8n

2 Answers

3 votes

-2(7n-6)+n=-3-8n

multiply the bracket by -2

-2(7n)-2(-6)+n= -3-8n

-14n+12+n= -3-8n

-14n+n+12= -3-8n

-13n+12= -3-8n

Move -8n to the other side. Sign changes from -8n to 8n.

-13n+8n+12= -3-8n+8n

-5n+12= -3

move +12 to the other side

sign changes from +12 to -12

-5n+12-12= -3-12

-5n= -15

Divide by -5

-5n/-5= -15/-5

n= 3

Answer : n= 3

User Ranty
by
6.1k points
1 vote

N = 3

Work is attached in the image provided.

What’s -2(7n-6)+n=-3-8n-example-1
User Elya
by
5.9k points